Cytopathology of bronchoalveolar lavages in COVID___19 pneumonia: A pilot study. Issue 8 (10th March 2021) - Canini, Valentina; Bono, Francesca; Calzavacca, Paolo; Capitoli, Giulia; Foti, Giuseppe; Fraggetta, Filippo; Galimberti, Stefania; Gianatti, Andrea; Giani, Marco; Nasr, Ahmed; Paciocco, Giuseppe; Pagni, Fabio; et al.
Abstract : BACKGROUND: Bronchoalveolar lavage (BAL) in patients with severe coronavirus disease 2019 (COVID‐19) may provide additional and complementary findings for the management of these patients admitted to intensive care units (ICUs). This study addresses the cytological features of the infection and highlights the more influential inflammatory components. The correlation between pathological variables and clinical data is also analyzed. METHODS: The authors performed a retrospective analysis of the cytopathological features of BAL in 20 COVID‐19 patients and 20 members of a matched cohort from a critical ICU who had acute respiratory distress syndrome caused by other pulmonary conditions. RESULTS: A comparison of the controls (n = 20) and the COVID‐19 patients (n = 20) revealed that the latter had a higher neutrophil count (median, 63.8% of the cell count) with lower percentages of macrophages and lymphocytes. An increase in the expression of CD68‐positive, monocytic multinucleated giant cells (MGCs) was reported; megakaryocytes were not detected on CD61 staining. Perls staining showed isolated elements. In situ RNA analysis demonstrated scattered chromogenic signals in type II pneumocytes. An ultrastructural analysis confirmed the presence of intracytoplasmic vacuoles containing rounded structures measuring 140 nm in diameter (putative viral particles). In COVID‐19 patients, the clinicopathological correlation revealed a positive correlation between lactate dehydrogenase values and MGCs ( r = 0.54). CONCLUSIONS: The analysis of BAL samples might be implemented as a routine practice for the evaluation of COVID‐19 patients in ICUs in the appropriate clinical scenario. Additional studies using a larger sample size of patients who developed COVID‐19 during the second wave of the epidemic in the autumn of 2020 are needed to further support our findings. Abstract : An analysis of the cytological features of bronchoalveolar lavage samples can provide useful information for the management of coronavirus disease 2019 patients in the intensive care unit.